Transcendental Communication in the Perang Topat Ritual: An Educational Analysis of Local Wisdom Values in Lingsar Village, West Lombok - Nujumudin, Nujumudin; Wahid, Abdul; Kadri, Kadri (Jurnal Ilmiah Profesi Pendidikan, 2024)
The Perang Topat ritual, a significant cultural tradition in Lingsar Village, West Lombok, is rooted in the Sasak community's local wisdom and spiritual beliefs. This research explores the importance of transcendental communication within this ritual and its educational implications for preserving local wisdom values. The study aims to analyze how transcendental communication in the Perang Topat ritual conveys and reinforces educational values that contribute to character building and cultural preservation. A qualitative research method was employed, using ethnographic techniques to gather data through participant observation, in-depth interviews, and documentation. Data analysis was conducted using an interpretive approach to uncover the deeper meanings and educational aspects of the ritual. The results reveal that the transcendental communication within the Perang Topat ritual plays a crucial role in instilling values such as mutual respect, tolerance, and spiritual connection among participants. The conclusion highlights that the ritual not only serves as a medium for spiritual and cultural expression but also as an educational tool for the younger generation. The implications of this research emphasize the need for integrating local wisdom values into formal education to preserve and promote cultural heritage.